Formulasi Dan Uji Mutu Fisik Sediaan Spray Gel Ekstrak Etanol Daun Nipah (Nypah fructicans. Wurmb) Sebagai Terapi Pengobatan Luka Sayat Terhadap Kelinci (New Zealand White) - Luthfia Dhiyaul Amalia; Danang Raharjo; Anita Dwi Septiarini (Lembaga Pengembangan Kinerja Dosen, 2023)
Cuts are defined as a form of damage or loss of body tissue caused by a sharp object. Incision wounds are also called incision wounds which are a type of acute wound. The method used in this research is an experimental method which aims to determine the presence of wound healing activity of extract and spray gel of nipah leaf extract (Nypa fruticans. Wurmb) as well as test the physical quality of spray gel preparation using New Zealand White (male) rabbits. There were 4 test animals divided into 4 groups, the sample was divided into 4 groups, namely the positive control group with Hansaplast spray and the negative control spray gel preparation without extract, the treatment group Nipah leaf extract gel spray (Nypa fruticans. Wurmb) with extract concentration 2 %,3%,5%. In nipah leaves (Nypa fruticans. Wurmb) there are compounds such as alkaloids, flavonoids, and saponins. This study proved that the ethanol extract of nipah leaves (Nypa fruticans. Wurmb) could be used as an anti-inflammatory, the result was that the ethanol extract gel preparation of nipah leaves (Nypa fruticans. Wurmb) had activity towards wound healing in rabbits